ASSESSMENT OF BREEDING POTENTIAL OF TOMATO (LYCOPERSICON ESCULENTUM MILL.) GERMPLASM USING D2 ANALYSIS - MEENA, OMPRAKASH; BAHADUR, VIJAY (The Bioscan, 2013)
The present investigation was carried out at Vegetable Research Farm, Department of Horticulture, SHIATS, Allahabad during 2012-13. All the genotypes were grouped into six clusters based on D2 values, which exhibited no association between geographical and genetic divergence. The intra-cluster distance was maximum for cluster V (10192.68) and minimum for cluster III (0). The maximum distance at inter-cluster level was between cluster III and cluster VI (47922.37) followed by clusters I and VI (44098.14) which may serve as a potential genotypes for hybridization programme. On the basis of mean performance of different clusters, genotypes having maximum flower clusters/ plant (17.48), flowers/plant (97.62), fruit weight (55.94g) and radial diameter of fruit (55.62mm) were observed in cluster VI. Genotypes having maximum fruit yield (1920.98g) along with maximum polar diameter of fruit (48.85mm) and minimum leaf curl incidence per cent (25.68) were recorded in cluster III. The genotypes of the cluster III for highest mean yield per plant along with minimum leaf curl incidence percent can be utilized as donor parent for enhancing the yield and minimum leaf curl incidence percent of other accessions grouped in a cluster in F1s and can be fixed by selecting transgressive segregants followed by continued selection in advance generations which may lead to development of high yielding varieties with desired component characters.